Steady-State Analysis and Comparison of Control Strategies for PMSM. (14th December 2015) - Agrawal, Jyoti; Bodkhe, Sanjay
Abstract : Permanent Magnet Synchronous Motor (PMSM) has been considered as the best choice for numerous applications. To make PMSM a high performance drive, effective control system is required. Vector control is accepted widely due to its decoupling effect but it is not the only performance requirement. Additional control methods such as constant torque angle control (CTAC), optimum torque per ampere control (OTPAC), unity power factor control (UPFC), constant mutual flux linkages control (CMFLC), and angle control of air gap flux and current phasor (ACAGF) can also be implemented. This paper therefore presents some important control strategies for PMSM along with merits and limitations which provide a wide variety of control choices in many applications. The performance characteristics for each strategy under steady state are modelled and simulated in MATLAB environment. Based on the simulation results, a conclusion is drawn that OTPAC is superior in normalized torque per unit normalized stator current (T e n / i s n ) ratio whereas UPFC yields very lowT e n / i s n ratio. In addition, performances of these control strategies are compared, which is a key to select optimum strategy depending on requirements. Based on the comparative study, it can be concluded that CMFLC is superior to CTAC, ACAGF, OTPAC, and UPFC. Hence, it can be a good control strategy to consider.